Application of guided inquiry student worksheet on additive materials to improve the science process skills of junior high school students - Nur Aida Salsabila Numa; Martini Martini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to describe the effectiveness of guided inquiry-based worksheets on additive material to improve students' science process skills. This type of research is a pre-experimental design with a one-group pretest-posttest design. The techniques of data collection a written tests and questionnaires. The research instrument was pretest-posttest sheets and student response questionnaires. The subjects in this study are 20 students of SMP Negeri 60 Surabaya class VIII-B in the odd semester of the 2021/2022 academic year. The data obtained were analyzed using quantitative descriptive methods. Based on the research that has been done, the results show that the students' science process skills increased significantly with the analysis of the N-gain average pretest-posttest score of 0.82 with the high category. It is 15% in the medium category and 85% in the high category. The analysis of the average N-gain indicators of science process skills also shows an increase in the high category of 0.82, which shows a percentage of 33% with the acquisition of categories, including aspects of presenting data and communication, and 67% with the acquisition of high categories formulate hypotheses, variables, and conclusions. Student responses to learning by applying guided inquiry-based worksheets showed a good response, with 96.75% in the very good category. Based on the research results, it can be said that guided inquiry-based worksheets can improve students' science process skills.